Effects of gestational age at birth on health outcomes at 3 and 5 years of age: population based cohort study. (1st March 2012) - Boyle, Elaine M; Poulsen, Gry; Field, David J; Kurinczuk, Jennifer J; Wolke, Dieter; Alfirevic, Zarko; Quigley, Maria A
Abstract : Objective To investigate the burden of later disease associated with moderate/late preterm (32-36 weeks) and early term (37-38 weeks) birth. Design Secondary analysis of data from the Millennium Cohort Study (MCS). Setting Longitudinal study of infants born in the United Kingdom between 2000 and 2002. Participants 18 818 infants participated in the MCS. Effects of gestational age at birth on health outcomes at 3 (n=14 273) and 5 years (n=14 056) of age were analysed. Main outcome measures Growth, hospital admissions, longstanding illness/disability, wheezing/asthma, use of prescribed drugs, and parental rating of their children's health. Results Measures of general health, hospital admissions, and longstanding illness showed a gradient of increasing risk of poorer outcome with decreasing gestation, suggesting a "dose-response" effect of prematurity. The greatest contribution to disease burden at 3 and 5 years was in children born late/moderate preterm or early term. Population attributable fractions for having at least three hospital admissions between 9 months and 5 years were 5.7% (95% confidence interval 2.0% to 10.0%) for birth at 32-36 weeks and 7.2% (1.4% to 13.6%) for birth at 37-38 weeks, compared with 3.8% (1.3% to 6.5%) for children born very preterm (<32 weeks). Similarly, 2.7% (1.1% to 4.3%), 5.4% (2.4% to 8.6%), and 5.4% (0.7% to 10.5%) of limiting longstanding illness at 5 years were attributed to very preterm birth, moderate/late preterm birth, and early term birth. Conclusions These results suggest that health outcomes of moderate/late preterm and early term babies are worse than those of full term babies. Additional research should quantify how much of the effect is due to maternal/fetal complications rather than prematurity itself. Irrespective of the reason for preterm birth, large numbers of these babies present a greater burden on public health services than very preterm babies.